Studi Eksplorasi Budaya Sekolah SMP Negeri 3 Lubuk Pakam - Lidya Ardiyan; Zainuddin Lubis; Wanapri Pangaribuan; Osberth Sinaga (Journal on Education, 2023)
The importance of school culture as a school personality is the basis for the formation of norms, values, and performance in schools. The research was conducted using Mix Methods, through interviews and an inventory survey of school culture to school principals and teachers at SMPN 3 Lubuk Pakam, a total of 45 people. The results of the interviews show that the principal, teachers and staff feel comfortable and have the support of one another. the school culture inventory survey also shows that the school culture is in a very good category, (X=145.62). Human Relations Orientation, Open System, Internal Process and Rational Purpose are all in good category. Each orientation is significantly correlated with school culture, internal process orientation (R=0.78), open system orientation (R=0.865), rational goal orientation (0.839) and human relations orientation (R=0.660).